2021
DOI: 10.3389/fmech.2021.681120
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Technique Investigation of a Biomimetic Insect Tarsal Adhesive Fluid

Abstract: There is substantial motivation to develop novel adhesives which take advantage of the superior adhesive strength and adaptability of many natural animal adhesives; however, the tools typically used to study these mechanisms are incapable of determining the precise interactions of molecules at an adhesive interface. In this study, a surface specific, order sensitive vibrational spectroscopy called sum frequency generation (SFG) is, for the first time, combined with multiple bulk characterization techniques to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The complexity of biological tarsal fluid makes it difficult to reproduce the properties of this secretion using artificial-hydrocarbon-based components because the artificial fluid only mimics a part of this complex mixture, which might be surface-specific. Additionally, the mimicking quality of the other physical properties of natural secretions in biomimetic adhesive fluids remains unknown [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of biological tarsal fluid makes it difficult to reproduce the properties of this secretion using artificial-hydrocarbon-based components because the artificial fluid only mimics a part of this complex mixture, which might be surface-specific. Additionally, the mimicking quality of the other physical properties of natural secretions in biomimetic adhesive fluids remains unknown [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence showing the non-Newtonian nature of adhesive fluid has only recently been confirmed [105]. Current tribological models revealed that both the interfacial interactions between the fluid and substrate as well as the chemistry of the bulk play an equally important role for establishing shear-thinning properties [105,291]. Therefore, further nano-tribological investigations are needed to gain additional insights into the origin of the observed friction forces of various insect species.…”
Section: Discussionmentioning
confidence: 99%